Farmland Preservation and Urban Expansion: Case Study of Southern Ontario, Canada - Caldwell, Wayne; Epp, Sara; Wan, Xiaoyuan; Singer, Rachel; Drake, Emma; Sousa, Emily C. (Frontiers in Sustainable Food Systems, 2022)
Farmland is an essential resource for the sustainability and security of human food systems. Preserving an agricultural land base is critical, as it is significantly affected by local, national, and global urbanization. This research introduces a case of farmland preservation in southern Ontario. This area contains some of Canada's most finite and productive soils but has an agricultural system facing enormous pressure from urban expansion. This paper reviews the farmland preservation policy framework within Ontario and provides insight into the role of different levels of government in protecting this critical resource. It also provides data at a regional level that provides the basis to evaluate the success of provincial and local policies. By tracking agricultural land conversion through local Official Plan Amendments (OPAs), this study documents farmland loss across southern Ontario between 2000 and 2017. Implemented and approved by local government and designed with public input, municipal Official Plans outline and describe land-use planning policies on how municipalities should use lands to meet community needs and desires. OPAs are formal and legally binding administrative changes to a municipal Official Plan decided through an open public process, which are required to change local land-use designations that conform with the long-term vision for growth and physical development. These OPAs may include the conversion of farmlands for non-farm uses (or, in contrast, the protection of agricultural lands). Over time, they will reveal the loss of farmlands in each community for different uses (and reflect changing priorities). Using OPAs to track the conversion of prime agricultural land is an innovative and rigorous methodological contribution, given the lack of data documenting long-term changes to the availability of agricultural lands and the impacts of urbanization on farmland conversion. Measuring farmland loss with this approach can be transferred and applied to contexts where municipalities are the entities responsible for agricultural land-use planning, outside of Ontario and beyond. Data from 36 counties/regions shows that the provincial policies and local planning framework have worked in tandem to affect the agricultural land base in southern Ontario significantly. In Central Ontario, the most urbanized area of Canada, the Province's Greenbelt Plan has significantly reduced the rates of farmland loss since 2005, while the Growth Plan and other policies contributed to enhanced municipal control over agricultural land conversion. Specifically, the Inner Ring municipalities have played increasingly active roles in agricultural land protection with both planning approaches and local initiatives. Outer Ring municipalities have seen increasing urbanization pressure. Data on farmland loss for non-agricultural use showed large-scale municipal-led urban boundary expansions and small-scale individual applications on policy changes. In Western Ontario, over the past two decades, there has been no obvious upward or downward trend of farmland loss. Most of the farmland conversion cases in this region were small-scale applications to create small lots on existing agricultural land to allow non-agricultural uses such as commercial, recreational, residential, and agricultural-related facilities. Since 2000, Southeastern Ontario, which has the smallest provincial share of prime agricultural land, has experienced limited farmland loss, consisting primarily of small-scale, individual applications on land-use re-designations (partially reflecting reduced acreages of prime agricultural land). The provincial policy impact on farmland preservation is not as evident in this region. The findings and methodology of this study contribute to the groundwork on farmland availability and land-use planning policy development and research by providing a baseline enumeration of farmland availability and the effect of farmland protection policies at provincial and municipal levels within Ontario's land use planning regime.